Evaluasi Program Percepatan Penurunan Stunting di Wilayah Kerja Puskesmas Baqa Samarinda Seberang - Kresnina Kresnina; Khoffifah Khoffifah; Lisdawati Lisdawati; Enos Paselle (Jurnal Syntax Admiration, 2024)
The purpose of the study is to describe and analyze the results of the evaluation of policies to accelerate stunting reduction and identify their impact in the region. This research uses qualitative descriptive method, to process data obtained from the research location. Qualitative descriptive research is generally to describe, explain, clarify, and describe the observed variables in accordance with the formulated problem so that researchers can describe the empirical reality related to the Acceleration of Stunting Reduction program in the work area of the Baqa Health Center, Samarinda Seberang District. Based on the research conducted, it can be concluded that the policy of Accelerating Stunting Reduction in Baqa Samarinda Seberang Village has not been fully effective because its utilization is still not optimal, although it is efficient in achieving the goal of improving the quality of infant/toddler health. Budgets relevant to stunting targets show good results, but need more attention for income equality and welfare. This policy has been evenly distributed and received a positive response from the government and the community, and its implementation is right on target. The positive impact of this policy can be seen from the reduction in stunting rates, ease of access to online programs, budget stability, and new adaptations needed for stunting handling in the future.